Qur'anic Interpretation and the Problem of Literalism: Ibn Rushd and the Enlightenment Project in the Islamic World - Sidiropoulou, Chryssi (Religions, 2015)
This article examines the claim that Ibn Rushd of Cordoba (Averroës, 12th century B.C.) is a precursor of the Enlightenment and a source of inspiration for the emancipation of contemporary Islamic societies. The paper critically discusses the fascination that Ibn Rushd has exercised on several thinkers, from Ernest Renan to Salman Rushdie, and highlights the problem of literalism in Qur'anic interpretation. Based on Ibn Rushd's Decisive Treatise (Fasl al-maqāl), the paper investigates Ibn Rushd's proposed division of (Muslim) society into three distinct classes. The main question here is whether there is a substantial link between the people of the Muslim community, given the three distinct kinds of assent (tasdīq) introduced by Ibn Rushd. I argue that if such a link cannot be supplied, then it is hard to see in Ibn Rushd an enlightened social model for today's Muslim societies. Furthermore, that the great majority of people are prevented from having any contact with non-literal interpretation of the Scripture and non-revealed ways of thinking. The latter position, though, does not seem to bring Ibn Rushd close to the Enlightenment. My analysis of religious language is inspired by Wittgenstein's position that the meaning of a term cannot be detached from its use. I suggest that given the different lives of people belonging to Ibn Rushd's different classes, the terms they use can mean quite different things. This argument in fact weakens Ibn Rushd's association with the Enlightenment.